Contribution to the knowledge of the spring butterfly fauna of the southern Anti-Atlas region, Morocco (Lepidoptera: Papilionoidea) - R. Verovnik; S. Beretta; M. Rowlings (SHILAP)
Data from eight butterfly surveys, mostly within the last 10 years, were combined to improve the knowledge of the distribution of butterflies in the Anti-Atlas region of Morocco. The records from 40 localities are presented and discussed. A total of 54 species were observed, closely matching the known butterfly fauna of the region. Interesting records for the following species are discussed in detail: Papilio saharae, Zerynthia rumina, Euchloe falloui, Colotis chrysonome, Colotis liagore, Callophrys avis, Cigaritis allardi, Tarucus rosaceus, Azanus ubaldus, Plebejus allardi, Melitaea deserticola, and Spialia doris. Of these Colotis liagore is recorded for the first time for Morocco, and two eremic species known only from a few localities are shown to be possible residents in the lower Draa Valley in the Assa region: Colotis chrysonome and Azanus ubaldus. Although we add valuable new information on the distribution of butterflies in Morocco more systematic research would probably yield many additional interesting records.